YAP at the progression of inflammation - Chen, Libin; Jin, Xintong; Ma, Jian; Xiang, Bo; Li, Xiayu (Frontiers in Cell and Developmental Biology, 2023)
Yes-associated protein (YAP) is a transcriptional regulator that affects cell proliferation, organ size and tissue development and regeneration, and has therefore, been an important object of study. In recent years, there has been an increasing research focus on YAP in inflammation and immunology, and the role of YAP in the development of inflammation and in immune escape by tumors has been progressively elucidated. Because YAP signaling involves a variety of different signal transduction cascades, the full range of functions in diverse cells and microenvironments remains incompletely understood. In this article, we discuss the complex involvement of YAP in inflammation, the molecular mechanisms through which it exercises pro- and anti-inflammatory effects under different conditions, and the progress achieved in elucidating the functions of YAP in inflammatory diseases. A thorough understanding of YAP signaling in inflammation will provide a foundation for its use as a therapeutic target in inflammatory diseases.